Draft Annual Plan 2001-2002 Government of Bihar - Planning Commission (Planning Commission, 2001)
With the carving out of the State of Jharkhand with 18 districts of undivided Bihar, on the 15th November, 2000 the State of Bihar now comprises 37 districts with an area of 94,163 sq. kms. and a population of 64.53 millions (1991 census). The population of State now constitutes about 7.6 percent of the country with about 3 percent of the geographical area of the country. This adverse land man ratio is reflected in the high density of population which is 685 per sq. km. as against 267 for the country. The State of Bihar now comprises an alluvial plains divided into two unequal regions North and South, by the river Ganga. The North Bihar covers an area of 0.54 lakh sq.km, while the South Bihar an area of 0.40 lakh sq. kms. According to the 1991 census, these regions had population of 40.1 and 24.1 millions with density of population of the order of 761 and 609 respectively. Undivided Bihar registered a decennial rate growth of population of23.54 percent during the decade 1981-91 which was marginally lower than the country as a whole.
Planning and Development Department